Fermentation and kinetic studies on laccase production by pycnoporus sanguineus / Muhammad Naziz bin Saat - Saat, Muhammad Naziz (2013)
Laccase (benzenediol: oxygen oxireductase, EC 1.10.3.2) is an extracellular enzyme that belongs to the blue multi-copper oxidases group. The broad specificity enzyme has the ability to oxidize wide range of aromatic compound especially phenolic compounds through radical-catalyzed mechanism involving four electrons reduction of oxygen molecule into water. Hence, laccase has been used in many biotechnological applications especially in pulp and paper industry, wastewater treatment, bioremediation, biosensor, etc. Laccase is mostly produced by white rot fungi which belong to the basidiomycetes. In this study, laccase was produced by a white rot fungus Pycnoporus sanguineus using submerged fermentation. Medium improvement for laccase production using shake flasks, the effects of yeast extract, malt extract and peptone were tested using two level full factorial design. The effect of malt extract was significant in improving extracellular laccase production. Different initial glucose concentrations tested did not significantly improved laccase production in the shake flasks after seven days cultivation. The effects of agitation speed and flask type on laccase production in shake flask was studied. Highest laccase productivity was obtained when the fungus was cultivated in the baffled flasks at 170 rpm. However the used of baffled flasks at higher agitation speeds resulted in excessive cell growth on the wall which decreased the enzyme production. In the production of laccase using stirred tank reactor (STR) selected culture variables were optimized using response surface methodology. The optimization process was performed in two stages viz screening experiment and followed by the optimization. The effects of selected operating variables namely iii agitation rate (rpm), aeration rate (L min-1) and pH were screened using two level full factorial design. Agitation rate and pH which significantly influenced laccase production in the screening experiment were furthered optimize using face-centered central composite design (FCCCD). Based on the FCCCD experiments, the predicted maximum laccase activity was 67.2 U L-1. Validation experiments using optimized conditions (agitation 600 rpm, pH 4.43 and aeration 1.0 L min-1) yielded average laccase production of 62.9 ± 4.9 U L-1. The kinetics of laccase production in shake-flask and stirred tank reactor were successfully modelled using unstructured kinetic model. The differential equation was solved using non linear regression method in order to obtain the kinetic parameters for biomass (X), laccase (P) and glucose content (S). Simulated model and experimental data showed good agreement. Based on the kinetic studies, laccase production increases with the depletion of glucose and when biomass growth has reached stationary phase. Thus, the laccase production in this fungal strain can be classified as non growth related. Partial purification of laccase was performed in three steps including ammonium sulfate precipitation, desalting and protein fractionation. Packed column was used in gel chromatography studies with Sephadex G-25 and G-75 as gel matrix for the column separation in desalting and protein fractionation, respectively. The purification fold value for the ammonium precipitation, Sephadex G-25 and Sephadex G-75 were 1.1, 3.8 and 5.1, respectively. Based on SDS PAGE analysis, the protein bands from the purified sample were located within 66 to 97 kDa range.